Excellent visible-light-driven photocatalytic performance of Cu2O sensitized NaNbO3 heterostructures. (27th August 2015) - Fan, Mingshan; Hu, Bo; Yan, Xu; Song, Chengjie; Chen, Tianjun; Feng, Yi; Shi, Weidong
<x xml:space="preserve">Abstract</x> Heterostructure complexes of Cu2O/NaNbO3 exhibited high catalytic activities on the degradation of methyl orange.